IMPLEMENTASI UNDANG-UNDANG NOMOR 2 TAHUN 2008 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 2 TAHUN 2011 TENTANG PARTAI POLITIK TERHADAP PERAN PARTAI POLITIK DALAM PROSES REKRUTMEN CALON LEGISLATIF (PERBANDINGAN REKRUTMEN POLITIK ANTARA PARTAI DEMOKRASI INDONESIA PERJUANGAN (PDI-P) DAN PARTAI GERAKAN INDONESIA RAYA (GERINDRA) - Rustanto, Naano; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
This study aims to determine how the implementation of political recruitment in Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties conducted by the Indonesian Party of Struggle (PDI-P) and the Greater  Indonesia  Movement  Party  (GERINDRA)  in  Sukoharjo  Regency  and the obstacles in the Recruitment process carried out by the Indonesian Party of Struggle (PDI-P) and the Greater Indonesia Movement Party (GERINDRA) in the Sukoharjo Regency.This study is a descriptive normative-empirical legal research. The types of data used are primary data and secondary data. The primary source used is direct interviews with the parties concerned. Secondary data sources are literature, legislation, journals, articles and materials from the internet and other related sources. The data collection technique used is a field study by going directly to the object of research and literature study to obtain a theoretical basis relating to research. Based on the results of the research and discussion, the PDI-P and Partai Gerindra recruitment was conducted based on Law Number 2 of 2011 concerning Political Parties, Law Number 8 of 2012 concerning DPR, DPD, and DPRD, as well as Party AD-ART. Recruitment is carried out through stages according to the Regulation of the Company. In recruiting PDI-P and Gerindra Party, they have obstacles, namely the factor of registering Human Resources and Political Conditions before the 2014 elections in Sukoharjo Regency.